Organizing Home Education Within Inclusive Education Frameworks - Ergasheva, Malika (Academicia Globe: Inderscience Research, 2025)
This article examines the process of organizing home education as a strategy for inclusive education for students with disabilities. The role of inclusive education policies in creating a flexible and individualized learning environment is emphasized, in which the process of home education serves as a complementary model, rather than a replacement for traditional education. It also focuses on practical issues faced by families and teachers, including problems accessing services, parental preparedness and social isolation.